Cost-effectiveness model for a hypothetical monotherapy vs standard of care in adult patients with treatment-resistant depression - Wang ST; Anderson IM; Mitchell D; Johnson SJ; Shiozawa A (Dove Medical Press, 2019)
Si-Tien Wang,1 Ian M Anderson,2 Dominic Mitchell,3 Scott J Johnson,1 Aki Shiozawa4,5 1Medicus Economics, LLC, Boston, MA, USA; 2Neuroscience and Psychiatry Unit, University of Manchester and Manchester Academic Health Science Centre, Manchester, UK; 3Medicus Economics, LLC, Repentigny, QC, Canada; 4Department of Health Policy and Management, Johns Hopkins Bloomberg School of Public Health, Baltimore, MD, USA; 5Global Outcome Research, Takeda Pharmaceuticals International, Inc., Deerfield, IL, USA Background: Patients with treatment-resistant major depressive disorder (TRD) have limited treatment options. We developed an early stage cost-effectiveness model of TRD to explore the potential value of a hypothetical monotherapy relative to the standard of care (SOC). The relative impacts of the monotherapy’s three differentiating features over SOC are explored: efficacy advantage, tolerability advantage, and price premium. Methods: We adapted an existing economic model of TRD to evaluate the cost-effectiveness of a hypothetical monotherapy for TRD with a 25% efficacy advantage, a 10% tolerability advantage, and a 50% price premium over SOC (selective serotonin reuptake inhibitor plus atypical antipsychotics [SSRI + AAP]). The model is a hybrid of a decision tree that captures patients’ outcomes after an 8-week acute treatment phase and a Markov model that simulates patients’ depression course through a 10-month maintenance phase. Sensitivity (deterministic and probabilistic) and scenario analyses were conducted to characterize the relative impacts of the monotherapy’s three differentiating features over SOC. Results: Over the 12-month time horizon, the hypothetical monotherapy is shown to dominate SOC; it generates lower costs and higher quality-adjusted life years in comparison to SSRI + AAP. Sensitivity and scenario analyses showed that this dominance depends largely on the monotherapy’s efficacy and tolerability advantages over SOC. Specifically, a monotherapy with ≥ 12% efficacy or ≥70% tolerability advantage (and a 50% price premium) will always be superior to SSRI + AAP. Between these two extremes, most profiles, nonetheless, generate incremental cost-utility ratios for the monotherapy, which fall below common payer willingness-to-pay thresholds. Conclusion: Our adaptation of an existing economic model of TRD provides a flexible platform for researchers to evaluate the efficacy/tolerability improvements required for a successful new TRD product and for decision-makers to assess the cost-effectiveness impact of uncertainties inherent in early stage product development in TRD. Keywords: treatment-resistant depression, cost-effectiveness, pharmacotherapy